Study on compatibility between social goal and personal goal in the Pig industry in China—An empirical analysis based on a cognitive perspective of farmers. Issue 4 (3rd July 2016) - Ma, Chenglin; Zhou, Deyi
Abstract: The paper discusses the problem whether the incentive compatibility exists between the social goal of large-scale pigs breeding and the personal goal of farmers satisfaction, which is based on the theory of the implementation of social goal and incentive compatibility. From the perspective in the cognitive subject of farmers, we mainly empirically investigate the effect of static cognitive factors and dynamic cognitive factors in choosing scale, and make an analysis of the satisfaction of farmers. The investigation results suggest that enhancing the cognitive of farmers in capital elements or in the supporting policy is incentive compatible to for realizing the social goal of large-scale pig breeding and the personal goal of increasing the farmers' satisfaction.